2021
DOI: 10.1021/acsami.1c11867
|View full text |Cite
|
Sign up to set email alerts
|

Heteroepitaxial Growth of High Optical Quality, Wafer-Scale van der Waals Heterostrucutres

Abstract: Transition metal dichalcogenides (TMDs) are materials that can exhibit intriguing optical properties like a change of the bandgap from indirect to direct when being thinned down to a monolayer. Well-resolved narrow excitonic resonances can be observed for such monolayers although only for materials of sufficient crystalline quality and so far mostly available in the form of micrometer-sized flakes. A further significant improvement of optical and electrical properties can be achieved by transferring the TMD on… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 67 publications
0
19
0
Order By: Relevance
“…From our previous work on MBE growth of MoSe 2 on hBN [25,26] we concluded that annealing of the samples after the growth helps to achieve continuous and smooth area of the first TMDC monolayer. The panels d)-f) of Fig.…”
Section: Resultsmentioning
confidence: 94%
“…From our previous work on MBE growth of MoSe 2 on hBN [25,26] we concluded that annealing of the samples after the growth helps to achieve continuous and smooth area of the first TMDC monolayer. The panels d)-f) of Fig.…”
Section: Resultsmentioning
confidence: 94%
“…To obtain larger area monolayers, epitaxial growth 17 , 18 and exfoliation by metal tapes 19 21 have been developed. Yet epitaxial TMD monolayers typically are polycrystalline, have high defect densities, large spatial inhomogeneities, and broad emission linewidths 17 , 18 .…”
Section: Introductionmentioning
confidence: 99%
“…3(l–o)). 99 Recently, Wei et al 100 have shown the complex nature of the nucleation and growth processes of MoSe 2 monolayers grown via MBE on mica. It has been observed that the 1T phase of MoSe 2 forms along with a comparable quantity of the 2H phase of MoSe 2 , where the 1T phase converts gradually into the stable 2H phase before the complete growth of the first monolayer.…”
Section: Recent Advances In Mbe-grown Transition Metal Dichalcogenidesmentioning
confidence: 99%
“…95 In a recent report, He et al 96 wafer through an in-depth examination of the optical studies (Figure 3(l-o)). 99 Recently, Wei et al 100…”
mentioning
confidence: 99%